2004
DOI: 10.1098/rsbl.2003.0149
|View full text |Cite
|
Sign up to set email alerts
|

Pollinator attractiveness increases with distance from flowering orchids

Abstract: Orchids are extraordinary among plants because many species are pollinated through sexual duplicity by producing flowers that mimic female insects to lure unsuspecting males. Previous work showed that sexual deception by the orchid Chiloglottis trapeziformis can have a negative impact on its wasp pollinator Neozeleboria cryptoides. We report that female wasps may be capable of mitigating the cost of the orchids' deception. Although male wasps quickly habituated to areas planted with unrewarding flower decoys, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 9 publications
0
28
0
Order By: Relevance
“…From recent studies on the mating behavior of solitary bees and wasps, we now know that female insects attract patrolling males by releasing specific chemical compounds (either in blends or specific compounds) that are capable of triggering genuine copulation attempts by the male insects when tested for their attractiveness on dummies. Besides, comparative analyses of the orchids' floral scent and the female insect sex pheromone have shown that the parasitic orchids use the same odor compounds as the females to deceive the males into pollinating the flowers (Schiestl et al 1999Ayasse et al 2003 ;Schiestl 2004 ;Mant et al 2005a ;Vereecken and Schiestl 2008) . In short, this interaction seems to constitute an illustrative case of mimicry that is primarily mediated by chemical signals.…”
Section: The Evolution Of Color Versus Odor In Orchid Mimicrymentioning
confidence: 99%
See 2 more Smart Citations
“…From recent studies on the mating behavior of solitary bees and wasps, we now know that female insects attract patrolling males by releasing specific chemical compounds (either in blends or specific compounds) that are capable of triggering genuine copulation attempts by the male insects when tested for their attractiveness on dummies. Besides, comparative analyses of the orchids' floral scent and the female insect sex pheromone have shown that the parasitic orchids use the same odor compounds as the females to deceive the males into pollinating the flowers (Schiestl et al 1999Ayasse et al 2003 ;Schiestl 2004 ;Mant et al 2005a ;Vereecken and Schiestl 2008) . In short, this interaction seems to constitute an illustrative case of mimicry that is primarily mediated by chemical signals.…”
Section: The Evolution Of Color Versus Odor In Orchid Mimicrymentioning
confidence: 99%
“…a The orchid parasite attracts its male insect host briefly without an attempt at copulation ( Pterostylis ; Taylor 1999 ; Lehnebach et al 2005) ; b The orchid parasite attracts its male insect host and triggers inspection behavior or a precopulatory routine ( Caladenia , Chiloglottis , Drakaea ;Peakall 1990 ;Peakall and Handel 1993 ;Schiestl 2004 ;Dickson and Petit 2006) ; c The orchid parasite triggers a host copulation attempt only ( Ophrys : Darwin 1862 ; Correvon and Pouyanne 1916 ;Kullenberg 1961 ;Ayasse et al 1997 ;Neiland and Wilcock 1998 ;Ayasse et al 2000 ;Vandewoestijne et al 2008 ;Vereecken, unpublished data;Geoblasta : Ciotek et al 2006) ; d The orchid parasite triggers host copulation attempt and ejaculation ( Cryptostylis: Schiestl et al 2004;Gaskett and Herberstein 2006 ;Gaskett et al 2008) . (Modified from Gaskett et al 2008) …”
Section: Fig 1a-dmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher outcrossing rates might be particularly advantageous to orchids because the packaging of pollen into pollinia effects high pollination efficiency in a single transfer, thus rendering orchids susceptible to geitonogamy and inbreeding depression. Comparative studies on outcrossing rates between food-deceptive and sexually deceptive species are lacking, but studies on thynnine wasp behavior have shown that males show an explicit site-based avoidance strategy after unsuccessful visits to female flower decoys (Peakall 1990;Wong et al 2004). This strategic avoidance of orchid patches might result in higher outcrossing rates in sexually deceptive species in comparison with food-deceptive ones, where foodseeking insects are duped and search for another nectar or pollen source (Peakall and Beattie 1996).…”
Section: Introductionmentioning
confidence: 99%
“…if the wingless females of the pollinator species are unable to obtain a mate when calling from within a patch of orchids (Wong and Schiestl 2002). The model may therefore be selected to avoid orchids, and field experiments suggest that females can respond by walking out of an orchid patch, which will resume their attractiveness for males (Wong et al 2004). Walking a few meters after unsuccessful calling may have evolved specifically in species exploited by orchids, however, experimental tests are lacking.…”
Section: Do Orchids Impose Selection On Their Pollinators?mentioning
confidence: 99%